2020
DOI: 10.22270/jddt.v10i2-s.3951
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Celecoxib Entrapped Guar Gum Nanoparticles Targeted for Oral Drug Delivery against Colon Cancer: An In-Vitro Study

Abstract: The present study is an attempt to synthesize nanosized guar gum carriers encapsulating celecoxib as the chemopreventive agent for experimental colorectal cancer (CRC).  Guar gum nanoparticles without celecoxib (eGGNPs) and celecoxib loaded guar gum nanoparticles (cGGNPs) were prepared by oil-in-water emulsification and in situ polymer crosslinking method. Electron microscopy, zeta potential and fourier transform infrared spectra analysis was used to affirm the size, stability and morphology of the nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Capecitabine-loaded guar gum and ethyl cellulose nanoparticles were synthesized by utilizing the emulsion solvent diffusion technique with minor adjustments 15,16 . Brie y, 15 mg guar gum was weighed and dissolved in 10 ml 0.2% polyvinyl alcohol.…”
Section: Preparation Of Guar Gum and Ethyl Cellulose Nanoparticles Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…Capecitabine-loaded guar gum and ethyl cellulose nanoparticles were synthesized by utilizing the emulsion solvent diffusion technique with minor adjustments 15,16 . Brie y, 15 mg guar gum was weighed and dissolved in 10 ml 0.2% polyvinyl alcohol.…”
Section: Preparation Of Guar Gum and Ethyl Cellulose Nanoparticles Co...mentioning
confidence: 99%
“…Nanosuspension was centrifuged and supernatant liquid was removed 17 . The nanosuspensions acquired were subjected to freeze-drying and preserved for subsequent analysis.…”
Section: Preparation Of Guar Gum and Ethyl Cellulose Nanoparticles Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the microbial degradation of GG in the large intestine may facilitate the release of the encapsulated drug from NPs, thereby decelerating celecoxib's release rate and prolonging its residual time before arrival at the colon. The results revealed that GG improved the targeted delivery of celecoxib and enhanced its permeability, slow release, and accumulation in the colon to inhibit the growth of Caco-2 colon cancer cells in a time-and concentration-dependent manner (Chandel et al, 2020). Additionally, Zarbab et al synthesized hydrogels loaded with MTX using GG, CS, and poly(vinyl alcohol) by solution casting technique, considerably enhancing MTX's anticancer activity against HCT-116 colon cancer cells with a prolonged 96% sustained release over 7.25 h. These investigations underscore GG-based NDDS as a potentially revolutionizing platform in antibacterial therapy, diabetes management, and cancer treatment (Zarbab et al, 2023).…”
Section: Guar Gummentioning
confidence: 99%
“…Most studies have been conducted primarily on the potential use of biopolymeric nanoparticles to deliver chemopreventive and chemotherapeutic agents [ 207 , 212 , 213 ]. For example, celecoxib has been successfully incorporated into guar gum nanoparticles to target colon cancer [ 214 ], as well as model drugs doxorubicin, 5-fluorouracil, rifampicin, rhodamine B, angiotensin II, antibiotic ciprofloxacin, and polyphenolic compounds, such as curcumin and caffeine. Furthermore, guar gum nanoparticles are suitable for oral as well as buccal, transdermal, and intravenous administration [ 215 ].…”
Section: Plant-based Biopolymeric Nanoparticles Used For Healthcare A...mentioning
confidence: 99%